2003
DOI: 10.1001/archpsyc.60.7.681
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole, an Antipsychotic With a Novel Mechanism of Action, and Risperidone vs Placebo in Patients With Schizophrenia and Schizoaffective Disorder

Abstract: Aripiprazole is effective, safe, and well tolerated for the positive and negative symptoms in schizophrenia and schizoaffective disorder. It is the first non-D2 receptor antagonist with clear antipsychotic effects and represents a novel treatment development for psychotic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
322
2
20

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 543 publications
(360 citation statements)
references
References 25 publications
14
322
2
20
Order By: Relevance
“…In a large, randomized, placebocontrolled study, both doses of AL evaluated (441 mg and 882 mg) administered every 4 weeks over the course of 12 weeks demonstrated robust efficacy compared with placebo (Meltzer et al, 2015). Results of that study are consistent with earlier studies of oral aripiprazole, which also showed efficacy for the acute treatment of schizophrenia at oral doses ranging from 10 to 30 mg per day (Potkin et al, 2003;Kane et al, 2002).…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…In a large, randomized, placebocontrolled study, both doses of AL evaluated (441 mg and 882 mg) administered every 4 weeks over the course of 12 weeks demonstrated robust efficacy compared with placebo (Meltzer et al, 2015). Results of that study are consistent with earlier studies of oral aripiprazole, which also showed efficacy for the acute treatment of schizophrenia at oral doses ranging from 10 to 30 mg per day (Potkin et al, 2003;Kane et al, 2002).…”
Section: Introductionsupporting
confidence: 79%
“…(Fleischhacker et al, 2014, Ishigooka et al, 2015Gopal et al, 2011;Turner et al, 2004, Potkin et al, 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from meta-analyses, systematic reviews, individual trials and longer term observational studies has indicated that significant weight gain is seen in many patients receiving psychotropic agents for the treatment of schizophrenia and bipolar disorder. Although no antipsychotic drug can be considered weight-neutral, as weight gain may occur in vulnerable patients during treatment with any atypical antipsychotic, greater mean weight gain does occur with olanzapine and clozapine [62][63][64][65].…”
Section: Plausibilitymentioning
confidence: 99%
“…In this context, the introduction of aripiprazole is of interest because while clinically it has all the features of an atypical antipsychotic (antipsychotic effect with very low motor side effects) (Kane et al, 2002;Potkin et al, 2003), it differs from all other antipsychotics in that it is a partial D 2 receptor agonist (Burris et al, 2002). Aripiprazole has been demonstrated to be a partial D 2 agonist in vitro as it acts like an antagonist in the presence of dopamine, while in dopamine's absence it increases dopamine transmission in several cell lines expressing cloned human dopamine D 2L receptors (Lawler et al, 1999;Burris et al, 2002;Shapiro et al, 2003).…”
Section: Introductionmentioning
confidence: 99%